Novel Alternative Ni-Based Binder Systems for Hardmetals - Mathias von Spalden; Johannes Pötschke; Alexander Michaelis (Crystals)
WC-Ni hardmetals, especially with the addition of Cr, are the first choice for wear parts in a corrosive environment. Despite Ni being studied as a metallic binder matrix in hardmetals for as long as Co, the mechanical properties achieved have consistently fallen behind those of their cobalt-containing counterparts. Due to the rapidly increasing demand for Co, its substitution is of increasing importance. In this study, various alloying elements that do not form strong carbides were systematically investigated as part of a binary Ni-based binder system for hardmetals. Solid and liquid phase sintering were compared by using field assisted sintering and a conventional SinterHIP furnace. The obtained hardmetals were analysed in terms of their microstructure, phases, sintering behaviour, and mechanical properties. The metals manganese, iron, and copper, as well as the metalloids silicon and germanium, were evaluated as additional binder constituents. Hardmetals with a binary Ni-based binder alloy were successfully prepared. The combination with Mn or Si showed the potential to significantly lower the necessary sintering temperature. In particular, Mn proved to be the most effective grain growth inhibitor among the investigated alloying elements.